KEMAJUAN GENETIK SAPI LOKAL BERDASARKAN SELEKSI DAN PERKAWINAN TERPILIH - Lusty Istiqomah (Pusbindiklat - LIPI, 2010)
The objectives of this research were (1) to estimate the breeding value in order to study the genetic progress of local beef cattle, and (2) to study the effectiveness of breeding method through selection program and assortative mating. The research was conducted at Genetic and Animal Breeding Laboratory, Animal Husbandry Faculty of Bogor Agricultural University from January to March 2006. Data of birth weight from assortative mating between 5 sires and 50 dams have been collected during 2000 to 2005. The data were analyzed using B-Gen program. Selection method that was practiced in this population showed in line with selection method using breeding value criteria. An assessment of genetic progress indicated positive both in annual mean direct genetic trends and annual maternaltrends for average birth weight. The average of inbreeding value from five generation was low (0.01%). It was concluded that genetic improvement through selection of growth traits and positive assortative mating was possible.